The Influence of Hebrew in the Qur'an: A Scientific Response on Abraham Geiger's Views - Muhaemin, Muhaemin; Majid, Abdul (Borneo International Journal of Islamic Studies, 2024)
This research focuses on examining Abraham Geiger's views regarding the Koran. This is important because it affects the purity of the Koran. The author uses descriptive analysis with a qualitative approach and verification methods. The results of the research are that according to Geiger, the Al-Qur'an available to Muslims is not an authentic, transcendent and original book, because many of its teachings are constructed and imitated from Judaism. These teachings include linguistic vocabulary in the Koran, religious concepts including views of life, rules and morals, and stories in the Koran. However, Geiger's views are not free from criticism. Several Muslim scholars have commented on and criticized his views. The aim is to show that the Koran is an authentic and original holy book and book of revelation, even though some of its teachings are contained in Jewish teachings because Islam does not exist in a vacuum without inhabitants, but is present in the midst of society with different cultures.